2020
DOI: 10.1111/bjh.17001
|View full text |Cite
|
Sign up to set email alerts
|

QuantiFERON‐TB Gold can help clinicians in the diagnosis of haemophagocytic lymphohistiocytosis

Abstract: CKG helped write the paper. S helped analyzed the genetic data. MGS provided patient history and clinical information. IR provided patient history and clinical information. HJM analyzed the data and wrote the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Several groups have observed that IFN‐γ is essential for the development of HLH 18,22,41–43 ; moreover, other studies have found that levels of IFN‐γ and/or CXCL9 are markedly elevated in animal models and patients with HLH. Indeed, measurement of IFN‐γ in PB using a commercial IFN‐γ release assay (e.g., quantiferon‐TB) may help to diagnose HLH 44 . In a mouse model, IFN‐γ was found to be essential for the development of HLH‐like pathology 42 .…”
Section: Ifn‐γ In Hlhmentioning
confidence: 99%
“…Several groups have observed that IFN‐γ is essential for the development of HLH 18,22,41–43 ; moreover, other studies have found that levels of IFN‐γ and/or CXCL9 are markedly elevated in animal models and patients with HLH. Indeed, measurement of IFN‐γ in PB using a commercial IFN‐γ release assay (e.g., quantiferon‐TB) may help to diagnose HLH 44 . In a mouse model, IFN‐γ was found to be essential for the development of HLH‐like pathology 42 .…”
Section: Ifn‐γ In Hlhmentioning
confidence: 99%
“…30 Moreover, previous studies found that indeterminate results of QFT-GIT (only one tube with specific peptides designed to stimulate CD4+ cells) or QFT Plus [two different tubes with specific peptides designed to stimulate CD4+ cells (TB1) and both CD4+ and CD8+ cells (TB2)], because of a high level of IFN-γ in the negative control tube, were obtained from patients with HLH, a not-so-rare (malignancy-associated HLH may occur in up to 1% of patients with HMs), lifethreatening, excessively inflammatory syndrome characterized by hyperactivation of macrophage and T-cells and causing fever, coagulopathy, cytopenia and liver function impairment, making it possible that QFT tests may help the diagnosis of HLH clinically, particularly in paediatric patients with primary HLH. 31,32 Our results together with these provide a fresh look at the role of high IFN-γ level of negative control result in the interpretation of QFT-GIT and the evaluation of progression to active TB in patients with HMs.…”
Section: Discussionmentioning
confidence: 67%
“…Recently, Merli et al described the use of an easy and widely available test, QuantiFeron-TB Gold (QFT-G) to detect patients with primary HLH. 36 As described before, IFN-γ play a key role in the pathogenesis of primary HLH (1, 10, 37). Merli et al showed that QFT-G test results were intermediate in all children with primary HLH.…”
mentioning
confidence: 84%
“…This was explained by the high serum IFN-γ levels, which characterized patients with primary HLH. 36 Even though some diseases, such as SLE and dermatomyositis may also present with high serum IFN-γ levels, this simple test may be a good diagnostic test to identify patients in whom a genetic mutation is suspected.…”
mentioning
confidence: 99%